2003
DOI: 10.1101/gr.1397903
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Functional Annotation of the Human Genome Using Artificial Transcription Factors

Abstract: We have developed a novel, high-throughput approach to collecting randomly perturbed gene-expression profiles from the human genome. A human 293 cell library that stably expresses randomly chosen zinc-finger transcription factors was constructed, and the expression profile of each cell line was obtained using cDNA microarray technology. Gene expression profiles from a total of 132 cell lines were collected and analyzed by (1) a simple clustering method based on expression-profile similarity, and (2) the shorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Of these 54 ZF modules, 31 were derived from DNA sequences in the human genome, and two were from those in the Drosophila genome (termed ''ToolGen modules''). These naturally occurring ZFs have been used repeatedly for the regulation of many genes in bacterial, yeast, and mammalian cells (Bae et al 2003;Lee et al 2003Lee et al , 2004Park et al 2003Park et al , 2005aKwon et al 2006;Yun et al 2008). The remaining 21 ZF modules were either selected from libraries of ZF variants using phage display (Barbas modules) (Dreier et al 2000(Dreier et al , 2001(Dreier et al , 2005Liu et al 2002) or produced by site-directed mutagenesis (Sangamo modules) , and were chosen to supplement the DNA-binding specificities of ToolGen modules.…”
Section: Zfn Design and Synthesismentioning
confidence: 99%
“…Of these 54 ZF modules, 31 were derived from DNA sequences in the human genome, and two were from those in the Drosophila genome (termed ''ToolGen modules''). These naturally occurring ZFs have been used repeatedly for the regulation of many genes in bacterial, yeast, and mammalian cells (Bae et al 2003;Lee et al 2003Lee et al , 2004Park et al 2003Park et al , 2005aKwon et al 2006;Yun et al 2008). The remaining 21 ZF modules were either selected from libraries of ZF variants using phage display (Barbas modules) (Dreier et al 2000(Dreier et al , 2001(Dreier et al , 2005Liu et al 2002) or produced by site-directed mutagenesis (Sangamo modules) , and were chosen to supplement the DNA-binding specificities of ToolGen modules.…”
Section: Zfn Design and Synthesismentioning
confidence: 99%
“…Recent advances in this field now allow one to construct randomized ZFP-transcription factor (ZFP-TFs) libraries that consist of tens of thousands of distinct transcription factors (31)(32)(33). These libraries have been used successfully to screen for components that induce diverse phenotypes of interest, such as cellular differentiation, stress resistance (31), over-expression of surface antigens (32), or resistance to Taxol, an anti-cancer agent (33). The selected ZFP-TFs could bind to and modulate expression of their target genes, which would generate phenotypes of interest.…”
Section: Introductionmentioning
confidence: 99%
“…showed that regulation of a single target gene within the entire human genome is achievable using a 6-finger ZFP transcriptional repressor that recognize an 18-bp site in the genome (32). The ability of ZFPs to activate or repress target gene expression was also exploited in a recent report, where the method was used to identify novel functional relationships among genes (33). …”
Section: Discussionmentioning
confidence: 99%